2022
DOI: 10.1097/cu9.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

How to reduce bacillus Calmette-Guérin discontinuation in patients with severe functional impairment

Abstract: Background Severe functional impairment is often considered a contraindication to intravesical therapy for nonmuscle-invasive bladder cancer (NMIBC). A tailored intravesical bacillus Calmette-Guérin (BCG) procedure was evaluated in high-risk (HR)-NMIBC patients with severe functional impairment. Materials and methods Patients with a Katz Index score of 2 or less and an initial diagnosis of HR-NMIBC with atraumatic insertion of a Foley-type indwelling catheter, bladder e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Di Gianfrancesco et al 50 showed that a tailored instillation procedure may reduce BCG discontinuation and side effects in patients with severe functional impairment. Serretta et al 51 out of 411 patients undergoing intravesical BCG with 1-year maintenance, reported that 215 (52.3%) only completed 1 year of treatment.…”
Section: How Does Bcg Perform In Real World Practice?mentioning
confidence: 99%
“…Di Gianfrancesco et al 50 showed that a tailored instillation procedure may reduce BCG discontinuation and side effects in patients with severe functional impairment. Serretta et al 51 out of 411 patients undergoing intravesical BCG with 1-year maintenance, reported that 215 (52.3%) only completed 1 year of treatment.…”
Section: How Does Bcg Perform In Real World Practice?mentioning
confidence: 99%